A randomised controlled trial of a case management approach to encourage participation in colorectal cancer screening for people with schizophrenia in psychiatric outpatient clinics: study protocol for the J-SUPPORT 1901 (ACCESS) study. Issue 11 (2nd November 2019) - Fujiwara, Masaki; Inagaki, Masatoshi; Shimazu, Taichi; Kodama, Masafumi; So, Ryuhei; Matsushita, Takanori; Yoshimura, Yusaku; Horii, Shigeo; Fujimori, Maiko; Takahashi, Hirokazu; Nakaya, Naoki; Kakeda, Kyoko; et al.
Abstract : Introduction: One of the reasons for the high mortality rate from cancer in people with schizophrenia is delay in diagnosis. Many studies have shown lower cancer screening rates in people with schizophrenia; however, there are no interventions for people with schizophrenia to increase cancer screening. Therefore, we developed a case management (CM) intervention to encourage participation in cancer screening. The purpose of this study was to examine the efficacy of CM to encourage participation in cancer screening for people with schizophrenia, with particular focus on colorectal cancer screening by faecal occult blood testing, compared with usual intervention (UI), namely, municipal public education. Methods and analysis: This is an individually randomised, parallel group trial with blinded outcome assessments. The participants will be randomly allocated to either the CM plus UI group or UI alone group in a 1:1 ratio using a web-based program at a data management centre. The primary end point of the study is participation in colorectal cancer screening in the year of intervention, which will be assessed based on municipal records. Ethics and dissemination: This study is performed in accordance with Ethical Guidelines for Medical and Health Research Involving Human Subjects published by Japan's Ministry of Education, Science, and Technology and the Ministry of Health, Labour, and Welfare and the modified Act on the Protection of Personal Information as well as the Declaration of Helsinki. This study was approved by the institutional ethics committee at the Okayama University Graduate School of Medicine, Dentistry, and Pharmaceutical Sciences and Okayama University Hospital on 23 April 2019 (approval number: RIN1904-003). The findings of this trial will be submitted to an international peer-reviewed journal. Trial registration number: UMIN000036017.